The Role of Social Media in Preventing Cyber Fraud in Barangay 165 Bagbaguin Caloocan City: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This chapter consists of the background of the study, Related literature, Related studies inthematic approach, Relevance of the Review of Related Literature and Studies to the presenthappening, Theoretical Framework, Conceptual Framework, Statement of the Problem,Assumption, Scope, and Delimitation of the study, Significance of the study, and definition ofterms.To complete this study properly, it is necessary to analyze the data collected and answer theresearch questions. As already indicated in the preceding chapter, data is interpreted in adescriptive form. This chapter discusses the interpretations of the data gathered by theresearchers. This chapter will show the procedure of reviewing data and drawing pertinentconclusions utilizing a variety of analytical techniques. The researchers can categorize,manipulate, and summarize data with the aid of interpretation to find answers to importantissues.This chapter presented the summary of findings, conclusion, and recommendation formulatedby the researchers. This study focused on The Role of Social media in Preventing CyberFraud at Barangay 165 Bagbaguin Caloocan city. The respondents are 40 Residents, and 10Law Enforcement agencies participated during the data-gathering phase. It focused on thefollowing: 1) Demographic profile of the respondents. 2) Respondents assess the Role ofSocial media in Preventing Cyber Fraud at Barangay 165 Bagbaguin Caloocan city. In termsof compromise, cyber scams, and information. 3) Problems encountered by the respondentsin Barangay 165 Bagbaguin Caloocan city. 4) Measure that may be proposed to address theproblems encountered by Barangay 165 Bagbaguin Caloocan city in Preventing Cyber fraud.The statistical tools used were frequency and percentage, weighted mean, ranking, and LikertScale.
Keywords: Criminology